2010
DOI: 10.1186/1532-429x-12-49
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cardiovascular magnetic resonance in myocarditis: comparison of MR and histological findings in an animal model

Abstract: BackgroundBecause Endomyocardial Biopsy has low sensitivity of about 20%, it can be performed near to myocardium that presented as Late Gadolinium Enhancement (LGE) in cardiovascular magnetic resonance (CMR). However the important issue of comparing topography of CMR and histological findings has not yet been investigated. Thus the current study was performed using an animal model of myocarditis.ResultsIn 10 male Lewis rats Experimental Autoimmune myocarditis was induced, 10 rats served as control. On day 21 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…rats on Day 21 after the induction of EAM, mapped the distribution of LGE using a seven-segment model of the LV, and reported that LGE was located mainly in the anterior and lateral LV walls, and was correlated with histopathology findings. 3,4 In the present study, CMR accurately identified the location and the extent of myocardial damage, which corresponded with the histopathological picture of myocarditis. These findings also correlate with typical findings in humans with myocarditis, showing a subepicardial distribution of LGE mainly in basal and mid-infero-lateral segments.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…rats on Day 21 after the induction of EAM, mapped the distribution of LGE using a seven-segment model of the LV, and reported that LGE was located mainly in the anterior and lateral LV walls, and was correlated with histopathology findings. 3,4 In the present study, CMR accurately identified the location and the extent of myocardial damage, which corresponded with the histopathological picture of myocarditis. These findings also correlate with typical findings in humans with myocarditis, showing a subepicardial distribution of LGE mainly in basal and mid-infero-lateral segments.…”
Section: Discussionmentioning
confidence: 91%
“…Significantly, the present study expands upon previous studies by providing new findings on myocarditis in a rat model. 3,4 First, in addition to…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CMR has also demonstrated excellent diagnostic capability for patients with suspected acute myocarditis, and EMB guided by CMR results may enhance the positive predictive value of this technique. 17,18 In our group, 5 of the patients had a CMR, but only in 1 of them, the most clinically stable case, it was part of the acute diagnostic process. All the other patients had the CMR after immunosuppression treatment and >10 days after admission.…”
Section: Discussionmentioning
confidence: 90%